Association of pregnancy outcomes in women with type 2 diabetes treated with metformin versus insulin when becoming pregnant - Shu-Fu Lin; Shang-Hung Chang; Chang-Fu Kuo; Wan-Ting Lin; Meng-Jiun Chiou; Yu-Tung Huang (BMC, 2020)
Abstract Background Metformin use in pregnancy is controversial because metformin crosses the placenta and the safety on the fetus has not been well-established. This retrospective study aimed to compare pregnancy outcomes in women with preexisting type 2 diabetes receiving metformin or standard insulin treatment. Methods The cohort of this population-based study includes women of age 20-44 years with preexisting type 2 diabetes and singleton pregnancies in Taiwan between 2003 and 2014. Subjects were classified into three mutually exclusive groups according to glucose-lowering treatments received before and after becoming pregnant: insulin group, switching group (metformin to insulin), and metformin group. A generalized estimating equation model adjusted for patient age, duration of type 2 diabetes, hypertension, hyperlipidemia, retinopathy, and aspirin use was used to estimate the adjusted odds ratio (aOR) and 95% confidence interval (CI) of adverse pregnancy outcomes. Results A total of 1166 pregnancies were identified in the insulin group (n = 222), the switching group (n = 318) and the metformin group (n = 626). The insulin group and the switching group had similar pregnancy outcomes for both the mother and fetus, including risk of primary cesarean section, pregnancy-related hypertension, preeclampsia, preterm birth (< 37 weeks), very preterm birth (< 32 weeks), low birth weight (< 2500 g), high birth weight (> 4000 g), large for gestational age, and congenital malformations. The metformin group had a lower risk of primary cesarean section (aOR = 0.57; 95% CI, 0.40-0.82) and congenital malformations (aOR, 0.51; 95% CI; 0.27-0.94) and similar risk for the other outcomes as compared with the insulin group. Conclusions Metformin therapy was not associated with increased adverse pregnancy outcomes in women with type 2 diabetes as compared with standard insulin therapy.